Association Between Central Obesity And Chronic Kidney Disease - Kabir, Md Rezwanul; Akter, Fahmida; Murshed, Syeda Ruquia; Chowdhury, Monzur Al Murshed; Simi, Nur Jahan (Journal of Preventive and Social Medicine, 2024)
Background: Chronic kidney disease (CKD) is increasingly recognized as a global public health concern which is one of the leading cause of death and disability. Central obesity increases the risk of developing major risk factors for chronic kidney disease like diabetes and hypertension. Methods: This case-control study was conducted between January and December, 2019. Fifty-five cases and fiftyfive age and sex matched controls were interviewed by a pretested semi-structured questionnaire. Medical records of the respondents were reviewed and a checklist was used to document after measuring height, weight, waist circumference and blood pressure. Results: The study showed that hypertension and diabetes mellitus were present in significantly higher proportions among the CKD respondents compared to the non-CKD respondents (P < 0.001). Cases were 11.5 times (OR 11.425; 95% CI 4.575-28.528) more likely to be hypertensive than controls. Cases were also 8.5 times (OR 8.469; 95% CI 3.119-23.000) more likely to be diabetic than controls. Among the all respondents, the proportion of central obesity was 40.9% while comparatively higher proportions were found in cases (45.5%) than in controls (36.4%). No significant association was found statistically between central obesity and chronic kidney disease. But diabetes mellitus and BMI were significantly associated with central obesity (P < 0.05). Centrally obese respondents were 2.5 times (OR 2.436; 95% CI 1.066-5.566) more likely to be diabetic than non-obese respondents. Lifestyle related risk factors such as consumption of tobacco both cigarette smoking and smokeless tobacco, alcohol consumption and body mass index (BMI) were also not associated with chronic kidney disease. Conclusion: As central obesity was associated with major risk factors of chronic kidney disease, so weight loss should be encouraged in obese subjects to decrease the risk of CKD. JOPSOM 2023; 42(1):7-13